1999
DOI: 10.1029/1998jc900050
|View full text |Cite
|
Sign up to set email alerts
|

Barents Sea seasonal ice zone features and processes from ERS 1 synthetic aperture radar: Seasonal Ice Zone Experiment 1992

Abstract: Abstract. Sea ice features and processes in the Barents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…However, since the variation in backscatter values within one ice type is too large or, in other words, the ranges of radar return intensities for different ice types overlap, one cannot base an analysis solely on the backscatter or higher moments of the backscatter [26]. Findings in the literature [27], therefore, suggest the use of additional image features for SAR-based ice-type classification, which take into account higher order textural features.…”
Section: Introductionmentioning
confidence: 95%
“…However, since the variation in backscatter values within one ice type is too large or, in other words, the ranges of radar return intensities for different ice types overlap, one cannot base an analysis solely on the backscatter or higher moments of the backscatter [26]. Findings in the literature [27], therefore, suggest the use of additional image features for SAR-based ice-type classification, which take into account higher order textural features.…”
Section: Introductionmentioning
confidence: 95%
“…Satellite and airborne SAR systems are used for a variety of tasks regarding retrieval of information about the state of the sea ice cover (e.g., Sandven et al, 1999). Examples are monitoring of ice drift and deformation, ice type classifica- Occasionally, it is difficult to achieve the optimal balance between the spatial res- The typical ice type classification is mainly based on ice thickness and macroscopic properties that are easy to identify visually (e.g., from the bridge of a ship).…”
Section: Retrieval Of Geophysical Information About Sea Ice Conditionmentioning
confidence: 99%
“…Note that the Svalbard sea ice barrier formed over the deep channel north of the Great Bank. In contrast, Sandven et al 's [1999] results from observations in March 1992 along ship tracks, crossing over an area in the Svalbard Bank region, showed that sea ice formed over shallow water locations but not over deep water. This contrast in the formation pattern of sea ice can be observed by QSCAT over an extensive sea surface in this region.…”
Section: Observation Of the Svalbard Sea Ice Barriermentioning
confidence: 80%
“…Thus bathymetry, through its control of the water distribution, and ice‐ocean‐atmosphere interactions can significantly impact ice formation at the sea surface. Indeed, Sandven et al [1999] observed that sea ice formation was related to bathymetric features through their influence on Arctic and Atlantic water masses.…”
Section: Introductionmentioning
confidence: 99%